Development of a science e-module based on contextual teaching and learning for primary school students - Tiasari Siregar; Saronom Silaban; Anita Yus (Inovasi Kurikulum, 2024)
The limited learning resources and the lack of attractiveness of the available learning resources are why students do not have a high enough interest in learning. The development of E-Modules to increase learning interest is carried out to overcome the problem of limited learning resources for students with illustrations and images that can attract their attention and be accessed anytime and anywhere. This study aims to produce a product in the form of an E-module of Science based on Contextual Teaching and Learning (CTL) for grade V Elementary School students that is feasible, practical and effective. The research method used is the Research on the Development of E-Modules of Science. The ADDIE development model comprises five stages: Analysis, Design, Development, Implementation and Evaluation (ADDIE). The feasibility test, practicality test and effectiveness test were carried out at Elementary School 105289 Kolam, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, with research subjects of grade V.A and V.B students of Elementary School 105289 Kolam, with data collection techniques in the form of observation, questionnaires and tests. The results of the study indicate that 1) the developed E-module of Science is declared feasible to be applied in the learning process; 2) The developed IPAS e-module is stated as practical by teachers with a very practical category and by students with a very practical category; and 3) The developed IPAS e-module is stated as effective. So, it is concluded that the developed IPAS e-module is feasible, practical and effective in improving learning outcomes. AbstrakKeterbatasan sumber belajar dan kurangnya menariknya sumber belajar yang tersedia menjadi alasan peserta didik tidak memiliki minat belajar yang cukup tinggi. Pengembangan E-Modul untuk meningkatkan minat belajar dilakukan untuk mengatasi masalah terbatasnya sumber belajar bagi peserta didik dengan ilustrasi dan gambar yang dapat menarik perhatian mereka serta dapat diakses kapan dan di mana saja. Penelitian ini bertujuan untuk menghasilkan produk berupa E-modul IPAS berbasis Contextual Teaching and Learning (CTL) untuk peserta didik kelas V Sekolah Dasar yang layak, praktis dan efektif. Metode penelitian yang digunakan adalah Penelitian Pengembangan E-Modul IPAS dengan model pengembangan ADDIE yang terdiri dari lima tahapan dimulai dari Analysis, Design, Development, Implementation and Evaluation (ADDIE). Uji kelayakan, uji kepraktisan dan keefektifan dilakukan di Sekolah Dasar 105289 Kolam Kecamatan Percut Sei Tuan Kabupaten Deli Serdang Provinsi Sumatera Utara dengan subjek penelitian peserta didik kelas V.A dan V.B Sekolah Dasar 105289 Kolam dengan Teknik pengumpulan data berupa observasi, angket dan tes. Hasil penelitian menunjukkan bahwa 1) E-modul IPAS yang dikembangkan dinyatakan layak untuk diterapkan dalam proses pembelajaran; 2) E-modul IPAS yang dikembangkan dinyatakan praktis oleh guru dengan kategori sangat praktis dan oleh peserta didik dengan kategori sangat praktis; dan 3) E-modul IPAS yang dikembangkan dinyatakan efektif. Sehingga disimpulkan E-Modul IPAS yang dikembangkan dinyatakan layak, praktis dan efektif untuk meningkatkan hasil belajar.Kata Kunci: contextual teaching and learning; CTL; e-modul; hasil belajar